The effect of reading literary fiction on theory of mind. - Werner, J. (The Young Researcher)
Theory of Mind is the ability to make inferences about the mental states of others. A positive cor- relation was drawn between theory of mind and language. Studies have shown that reading literary fiction positively impacts Theory of Mind abilities in adults, but no research has delved into a focus on younger age groups. This study investigates whether reading literary fiction increases Theory of Mind abilities in children. A quasi experimental quantitative method was conducted using matched sampling. Paired T-tests were run to compare pre and post test scores. The results indicate that reading literary fiction may cause an increase in children’s Theory of Mind abilities at least temporarily, emulating the effect it has in adults. This research is of relevance to the recent debates on the inclusion of fiction in school curriculums and emotional intelligence in business. Further research should be conducted to ensure a more representative population is tested; these findings can be used to inform future work in this area.